EPCT-06. PRECISION ONCOLOGY IN THE PEDIATRIC TARGETED THERAPY 2.0 PROGRAM. (1st June 2021) - Ecker, Jonas; Selt, Florian; Korshunov, Andrey; Capper, David; Dikow, Nicola; Hirsch, Steffen; Sutter, Christian; van Tilburg, Cornelis; von Deimling, Andreas; Jones, David T W; Pfister, Stefan M; Sahm, Felix; et al.
Abstract: Introduction: Precise diagnoses and robust detection of actionable alterations is required for individualized treatments. By using extended molecular diagnostics, the Pediatric Targeted Therapy (PTT) 2.0 program aims at the improvement of diagnostic accuracy and detection of actionable alterations for pediatric high-risk patients. The impact of these analyses on clinical management is reported. Methods: Pediatric patients with relapsed or progressive tumors after standard of care treatment were included, independent of histological diagnosis. Formalin fixed paraffin embedded material and a blood sample for germline correction were requested. DNA methylation array, targeted gene panel sequencing (130 genes), RNA and Sanger sequencing in selected cases, and immunohistochemistry (IHC) of selected markers (pERK, pAKT, pS6, PD-L1) were performed. A questionnaire-based follow-up was used to determine the clinical impact of the analysis. Results: We enrolled n=263 patients from February 2017 to February 2019. Complete molecular analysis was possible for n=260 cases (99%). The most common entities were brain tumors (n=172/260, 65%). In brain tumors, DNA methylation array alone allowed robust diagnostic classification (score of >=0.9) in n=104/172 cases (60%). Actionable targets as detected by copy number calculation, gene panel sequencing, RNA sequencing and IHC were found in n=94/172 (55%) brain tumor cases. The most common actionable targets in brain tumors were MAPK (pERK, BRAF fusions, BRAF V600E), mTOR (pS6), PI3K (pAKT), CDK4/6 (CDKN2A/B loss), and immune checkpoints (PD-L1). Pathogenic germline alterations with clinical relevance were identified in n=12/172 brain tumor cases (6.9%) and were confirmed by Sanger sequencing, 5/12 (41%) of which were previously unknown. Clinical follow-up of subsequent treatment and outcome are ongoing. Conclusion: The combination of next-generation diagnostics such as methylation arrays and targeted sequencing in addition to selected IHC markers added robust information with regard to diagnosis and actionable alterations. The impact on clinical decision-making and on outcome is currently being evaluated.